A modified Kiss, Marry, Kill game, a novel game-based learning activity for biology and anatomy and physiology students to learn and retain complex scientific concepts - Roberto Mariani; Emral Devany (Journal of Microbiology & Biology Education)
ABSTRACT This study introduces how a series of fun and interactive discussion board activities can enhance student engagement and understanding of important chemical and biological concepts in college biology and anatomy and physiology courses. The activity is a novel game-based learning approach based on a modified version of the “Kiss, Marry, Kill” (KMK) game, where students choose between course content-related choices provided (e.g., three types of cellular organelles—mitochondria, ribosomes, and nucleus) and explain their choices. By requiring students to evaluate and justify their choices, this method promotes critical thinking and collaborative learning in biology education. Participants also engage in discussions about these choices, fostering collaborative learning. This article details the implementation process, anticipated outcomes, and pedagogical benefits of this innovative approach.